Strategi Komunikasi Pemasaran B2B dalam Inovasi Medis Protesa Mata Berbasis Teknologi 3D (Studi Kasus PT. Tri Dimensi Indonesia dan RS. Mata Cicendo Bandung - Dalila, Ghina Khansa; Prabawani, Bulan; Darmasari, Ria (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the Marketing Communication Strategy for Business to Business (B2B) in 3D technology -based medical innovation developed by PT. Tri Dimension Indonesia in collaboration with RS. Mata Cicendo Bandung. Background Research is based on an increase in the needs of eye prosthesis in Indonesia and the low quality of conventional prosthesis which often causes patient discomfort. 3D printing innovation offers precision, fast and personal solutions, but the adoption is still limited due to communication and collaboration factors between institutions. The research method uses a qualitative approach with case study design, through in -depth interviews, participatory observations, and document analysis. Data analysis was carried out by pattern matching techniques using the Aidas (Attention, Interest, Desire, Action, Satisfaction) models to evaluate the effectiveness of B2B marketing communication strategies. The results showed that the communication strategy of PT. Tri Dimension Indonesia emphasizes personal interaction with Key Opinion Leader, clinical evidence -based presentations, and adaptive relational communication. At the action stage, contractual negotiations and technical support are key factors in strengthening adoption decisions. Whereas at the satisfaction stage, the sustainability of cooperation is maintained through clinical monitoring, after -sales service, and joint product development. Theoretically, this study expanded the application of the Aidas model into the context of the B2B health sector that is complex and based on high involvement decision making. Practically, research results can be a reference for the local health technology industry in designing effective marketing communication strategies to accelerate the adoption of medical innovation.